Using the indicator amino acid oxidation technique to study threonine requirements in horses receiving a predominantly forage diet. Issue 5 (14th June 2018) - Mok, Chan Hee; Levesque, Crystal L.; Urschel, Kristine L.
Abstract: Threonine has been reported to be the second limiting amino acid in typical equine diets, but its actual requirement has not been determined in horses. To evaluate amino acid metabolism and requirements, the indicator amino acid oxidation (IAAO) method has been successfully used in other species. The objective of this research was to estimate threonine requirements in mature horses fed timothy hay and concentrate in 4:1 ratio using the IAAO method. Six Thoroughbred mares (579.9 ± 46.7 kg) received each of 6 levels of threonine intake, 41, 51, 61, 70, 80 and 89 mg/kg BW/day, in a randomly determined order. Each study period was 7‐day long, and on day 6, blood samples were collected before and 90 min after feeding to measure amino acid concentrations using HPLC. On day 7, horses underwent IAAO procedures, which included a 2‐hr primed, constant intravenous infusion of [ 13 C]sodium bicarbonate to measure total CO2 production and a 4‐hr primed, constant oral administration of [1‐ 13 C]phenylalanine to estimate phenylalanine oxidation to CO2 . Blood and breath samples were collected to measure blood [ 13 C]phenylalanine, using GC‐MS analysis and breath 13 CO2 enrichment, using an infrared isotope analyser. Increasing threonine intake levels did not affect plasma phenylalanine oxidation by the ANOVA test ( p > 0.05) but resulted in a linear decrease in phenylalanine oxidation ( p = 0.04) without a breakpoint by the orthogonal linear contrast. This study is the first attempt to evaluate threonine requirements in horses by the IAAO method; however, threonine requirements are still unknown in mature horses at this time.